Cosmic ray 2H/1H flux ratio measurement with the AMS-02 experiment - Lordello, Vitor Diorio (2017)
The Alpha Magnetic Spectrometer (AMS-02) is a cosmic ray detector operating aboard the International Space Station (ISS) since May 2011. The identification of cosmic ray deuterium and hydrogen particles is the main goal of this work. Using the data collected by the AMS-02 experiment between May 2011 and May 2014 we provide the measurement of the 2H to the 1H ratio between 0.7 and 7 GeV/n. Cosmic rays are mainly composed of hydrogen nuclei. No significant amount of deuterium nuclei is expected to be released from galactic sources since they are destroyed rather than formed in thermonuclear reactions inside stars. As a consequence of their production history, they are part of a class of secondary stable nuclei that provide information on the propagation of cosmic rays in the galaxy. Despite their relevance for propagation studies, very few measurements of deuterium exist above 1 GeV/n, due to the poor isotopic separation capacity of previous experiments. For this reason, the deuterium to hydrogen flux ratio is a very important measurement to be carried out using the data collected by the AMS-02 experiment. The mass and the isotopic composition of cosmic-rays nuclei can be measured by the AMS-02 experiment using measurements of the momentum (provided by the tracker) and velocity of the particles (provided by the Time-of-Flight and the RICH). This analysis is one of the first to be focused on hydrogen isotopic composition with AMS-02 data, and our results are in fair agreement with a similar and independent analysis that has been carried out within the Collaboration.